Experimental analysis and finite element modeling of the piston-on-three balls testing of Y-TZP ceramic - Silva, P. C.; Moreira, L. P.; Alves, M. F. R. P.; Campos, L. Q. B.; Simba, B. G. [UNESP]; Santos, C. Dos (Associação Brasileira de Cerâmica, 2019)
The objectives of this study were to characterize and evaluate the physical and mechanical properties of an experimental zirconia for dental application and compare the biaxial flexural strength results with the finite element simulation (FEM). Yttria-stabilized tetragonal zirconia polycrystal (Y-TZP) ceramic samples were sintered at 1475 °C/2 h and characterized by X-ray diffraction, scanning electron microscopy, relative density, flexural strength using piston-on-three balls (P-3B) test and Young’s modulus. From the flexural strength results, numerical simulations were performed using Abaqus software. The complete model used 70216 elements, considering the components of the test. The results indicated full densification of sintered samples, ZrO2-tetragonal and ZrO2-cubic as crystalline phases, and average grain size of 0.6±0.2 μm. Mechanical characterization of sintered samples indicated Young’s modulus of 195±4 GPa, flexural strength of 1191±9 MPa and Weibull modulus m=16.3. FEM simulation indicated a flexural strength close to 1100 MPa, with a difference lower than 7% in relation to the experimental results. The results were compared associating the physical and mechanical properties of Y-TZP with its intrinsic phenomena such as tgm transformation and ferroelastic domain.

O objetivo deste estudo foi caracterizar e avaliar as propriedades físicas e mecânicas de uma zircônia experimental para aplicação odontológica e comparar os resultados da resistência à flexão biaxial com a simulação de elementos finitos (MEF). Amostras de zircônia tetragonal estabilizada com ítria (Y-TZP) foram sinterizadas a 1475 °C/2 h e caracterizadas por difração de raios X, microscopia eletrônica de varredura, densidade relativa, resistência à flexão usando teste de pistão em três bolas (P-3B) e módulo de Young. A partir dos resultados de resistência à flexão, foram realizadas simulações numéricas utilizando o software Abaqus. O modelo completo utilizou 70216 elementos. Os resultados apontaram para densificação total em amostras sinterizadas, ZrO2 tetragonal e cúbica como fases cristalinas, tamanho de grão de 0,6±0,2 μm, módulo de Young de 195±4 GPa, resistência à flexão de 1191±9 MPa e módulo de Weibull m=16,3. A simulação numérica indicou uma resistência à flexão próxima de 1100 MPa, com diferença menor que 7% em relação aos resultados experimentais. Os resultados foram comparados associando as propriedades físicas e mecânicas de Y-TZP com seus fenômenos intrínsecos, como a transformação tgm e o domínio ferroelástico.
Analise experimental e modelamento por elementos finitos de ensaio de flexão biaxial de cerâmica Y-TZP
Keywords: Y-TZP ceramics; mechanical properties; flexural strength; piston-on-three balls (P-3B) test; FEM simulation; toughening mechanisms; zircônia; resistência à flexão; teste de pistão em três bolas (P-3B); simulação MEF; mecanismos de tenacificação